Deciphering metabolic differentiation during Bacillus subtilis sporulation - Juan D. Tibocha-Bonilla; Jelani Lyda; Eammon Riley; Kit Pogliano; Karsten Zengler (Nature Communications)
Abstract The bacterium Bacillus subtilis undergoes asymmetric cell division during sporulation, producing a mother cell and a smaller forespore connected by the SpoIIQ-SpoIIIA (or Q-A) channel. The two cells differentiate metabolically, and the forespore becomes dependent on the mother cell for essential building blocks. Here, we investigate the metabolic interactions between mother cell and forespore using genome-scale metabolic and expression models as well as experiments. Our results indicate that nucleotides are synthesized in the mother cell and transported in the form of nucleoside di- or tri-phosphates to the forespore via the Q-A channel. However, if the Q-A channel is inactivated later in sporulation, then glycolytic enzymes can form an ATP and NADH shuttle, providing the forespore with energy and reducing power. Our integrated in silico and in vivo approach sheds light into the intricate metabolic interactions underlying cell differentiation in B. subtilis, and provides a foundation for future studies of metabolic differentiation.